Data-driven sudden cardiac arrest research in Europe: Experts’ perspectives on ethical challenges and governance strategies - Marieke A.R. Bak; Jelle C.H. Vroonland; Marieke T. Blom; Domagoj Damjanovic; Dick L. Willems; Hanno L. Tan; M. Corrette Ploem (Resuscitation Plus, 2023)
Background: Observational studies using large-scale databases and biobanks help improve prevention and treatment of sudden cardiac arrest (SCA) but the lack of guidance on data protection issues in this setting may harm patients’ rights and the research enterprise itself. This qualitative study explored the ethical aspects of observational SCA research, as well as solutions. Methods: European experts in SCA research, medical ethics and health law reflected on this topic through semi-structured interviews (N = 29) and a virtual roundtable conference (N = 18). The ESCAPE-NET project served as a discussion case. Findings were coded and thematically analysed. Results: The first theme concerned the potential benefits and harms (at individual and group level) of observational data-based SCA studies and included the following sub-themes: societal value, scientific validity, data privacy, disclosure of genetic findings, stigma and discrimination, and medicalisation of sudden death. The second theme involved governance through ‘privacy by design’, ‘privacy by policy’ and associated regulation and oversight. Sub-themes were: de-identification of data, informed consent (broad and deferred), ethics review, and harmonisation. Conclusions: Researchers and scientific societies should be aware that ethico-legal issues may arise during data-driven studies in SCA and other emergencies. These can be mitigated by combining technical data protection safeguards with appropriate informed consent policies and proportional ethics oversight. To ensure responsible conduct of data research in emergency medicine, we recommend the establishment of ‘codes of conduct’ which should be developed in interdisciplinary groups and together with patient representatives.